Discipline, motivation, and OB satisfaction on employee performance at PT XX - Setyawati, Novita; Giningroem, Dewisriwoelandari; Rohaeni, Heni (UiTM Cawangan Johor, 2023)
Humans are assets for companies that must be directed and guided to have the ability according to the desired expectations, integrity, loyalty, and high morale need to be applied to employees to have a sense of responsibility for work discipline, motivation, and job satisfaction they do. Poor work discipline, motivation, and job satisfaction can cause various problems in a company, such as employee performance. This study aims to determine whether work discipline, work motivation, and job satisfaction affect employee performance. The method used is the PLS method. All indicators of the work discipline variable have a significant negative effect on employee performance with a path coefficient of 0.476. Meanwhile, work motivation has a negative and insignificant effect on employee performance with a path coefficient of 0.065. Furthermore, the variable job satisfaction has no significant positive effect on employee performance with a path coefficient of 0.495